Pengaruh Komunikasi, Motivasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Dinas Pemadam Kebakaran Kabupaten Paser - Joharatul Isna; Misna Ariani; Imam Arrywibowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to determine the effect of Communcation, Motivation, and WorkEnvironment on Job Satisfaction of Paser Regency Fire Department Employees. The type of research usedis quantitative research. The sampling technique in this study was total / census sampling with apopulation of 88 employees, so the sample taken was all employees of the Paser Regency Fire Service,totaling 88 employees. The data collection method was carried out by distributing questionnaires. Thisstudy uses multiple linear regression with the help of SmartPLS in processing data. The results of thisstudy indicate that communication variables partially affect the job satisfaction of Paser Regency FireDepartment employees, motivation variables partially affect the job satisfaction of Paser Regency FireDepartment employees, and work environment variables partially affect the job satisfaction of PaserRegency Fire Department employees